2019
DOI: 10.1155/2019/9890716
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Metastatic Breast Carcinoma to the Thyroid Gland Histologically Mimicking C Cell Lesions

Abstract: The thyroid gland is an uncommon site of metastatic disease. Renal cell carcinoma is the most common primary source, while metastasis from breast carcinoma is very rare. However, given that thyroid nodules are more common in women, and women with a history of breast cancer are at higher risk of developing thyroid cancer, the possibility of metastatic breast carcinoma must be considered when evaluating a thyroid nodule. We present the case of a 67-year-old woman who presented with dysphonia and dysphagia second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Magers et al [6] found that metastatic thyroid cancer from breast cancer can cytologically and morphologically mimic primary thyroid cancer on FNAB. Additionally, metastatic breast cancer cells in the thyroid, which mimicked C cell hyperplasia and medullary thyroid carcinoma, were observed in the case of Ghias et al [5]. In our case, FNAB of thyroid showed malignant cells with enlarged nuclei.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Magers et al [6] found that metastatic thyroid cancer from breast cancer can cytologically and morphologically mimic primary thyroid cancer on FNAB. Additionally, metastatic breast cancer cells in the thyroid, which mimicked C cell hyperplasia and medullary thyroid carcinoma, were observed in the case of Ghias et al [5]. In our case, FNAB of thyroid showed malignant cells with enlarged nuclei.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have demonstrated that GATA3 and GCDFP15 expression were positively associated with breast carcinoma and breast cancer metastasis [15,16].GATA3 is superior to GCDFP15 in determining the breast origin [17,18]. Ghias et al [5] reported that thyroid metastases cells were positive for ER, GATA3, and were negative for GCDFP, TTF-1, TG and calcitonin. Similar result is also observed in our case.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations